Língua escrita e língua real: o que um corpus oral permite descobrir (Studia Iberystyczne, 2014)
THE WRITTEN LANGUAGE AND THE REAL LANGUAGE: WHAT AN ORAL CORPUS CAN REVEALStarting from an extensive oral corpus which is being collected, this paper focuses on how the oral language allows us to realize what languages really are and how they work beyond the formalized written dimension. It is our claim to show that it is language in use that better highlights many aspects which are impossible to understand only by an analysis of the traditional “linguistic system”. So we will verify how oral speech really performs sentences and its lexical and pragmatic elements.